The role of the thrombopoietin receptor MPL in myeloproliferative neoplasms: recent findings and potential therapeutic applications. Issue 6 (3rd June 2019) - Vainchenker, William; Plo, Isabelle; Marty, Caroline; Varghese, Leila N.; Constantinescu, Stefan N.
ABSTRACT: Introduction : Classical Myeloproliferative Neoplasms (MPNs) include three disorders: Polycythemia Vera (PV), Essential Thrombocythemia (ET) and Primary Myelofibrosis (PMF). MPNs are associated with constitutive activation of JAK2 leading to persistent cell signaling downstream of the dimeric myeloid cytokine receptors due to mutations in three genes encoding JAK2, calreticulin (CALR) and the thrombopoietin (TPO) receptor (MPL or TPOR). CALR and MPL mutants induce JAK2 activation that depends on MPL expression, thus explaining why they induce megakaryocyte pathologies including ET and PMF, but not PV. In contrast, JAK2 V617F drives all three diseases as it induces persistent signaling via EPOR, G-CSFR (CSF3R) and MPL. Areas Covered : Here, we review how different pathogenic mutations of MPL are translated into active receptors by inducing stable dimerization. We focus on the unique role of MPL on the hematopoietic stem cell (HSC), explaining why MPL is indispensable for the development of all MPNs. Last but not least, we describe how CALR mutants are pathogenic via binding and activation of MPL. Expert Opinion : Altogether, we believe that MPL is an important, but challenging, therapeutic target in MPNs that requires novel strategies to interrupt the specific conformational changes induced by each mutation or pathologic interaction without compromising the key functions of wild type MPL.